2022
DOI: 10.3390/foods11030410
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Impact of Solid-State Fermentation on Macronutrient Profile and Digestibility in Chia (Salvia hispanica) and Sesame (Sesamum Indicum) Seeds

Abstract: Fermentation of plant-based substrates with edible fungi enhances the nutrient profile and digestibility, but it has been scarcely applied to edible seeds, which are rich in healthy lipids. In this study, chia and sesame seeds were solid-state fermented with Pleurotus ostreatus, followed by drying and milling. Fermentation led to increased content of lipid and protein in both seeds’ products, and a change in fatty acid profile in favor of increased polyunsaturated fatty acids. Then, the samples were subjected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 53 publications
1
0
0
Order By: Relevance
“…In addition, fatty acid was increased after both rice fermentation. These results are in accordance with previous research that showed a slight increase in fatty acid after fermenting chia and sesame seeds [ 34 ]. An increase in fatty acids such as short-chain fatty acids in the fermented product cloud be attributed to microorganisms’ metabolism [ 35 ], producing SCFA (acetate, propionate, and butyrate) from carbohydrates and protein catabolism [ 36 , 37 ].…”
Section: Discussionsupporting
confidence: 93%
“…In addition, fatty acid was increased after both rice fermentation. These results are in accordance with previous research that showed a slight increase in fatty acid after fermenting chia and sesame seeds [ 34 ]. An increase in fatty acids such as short-chain fatty acids in the fermented product cloud be attributed to microorganisms’ metabolism [ 35 ], producing SCFA (acetate, propionate, and butyrate) from carbohydrates and protein catabolism [ 36 , 37 ].…”
Section: Discussionsupporting
confidence: 93%
“…The obtained FA profile of chia seeds is in line with those reported in earlier studies [5,54,55]. Similar tendencies regarding SFA, MUFA, and PUFA in fermented chia seeds were also found by Calvo-Lerma et al [12], who used edible fungi for SSF of chia. They also stated that unsaturated FA (UFA) are on the rise, whereas those with a saturated carbon chain are on the decline in most plant materials fermented with various microorganisms.…”
Section: Parameters Of Non-fermented and Fermented Chia Seedssupporting
confidence: 90%
“…However, the shells of seeds barely break down during the digestion process, impeding the release and absorption of nutrients [12]. Moreover, as was mentioned before, chia seeds contain such "antinutrients" as oxalates, tannins, and phytates, which can interact with nutrients, preventing their absorption [13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Solid-state fermentation has been recently explored as a strategy to preserve/enhance the nutritional value of legumes with promising results in obtaining new ingredients (Calvo-Lerma et al, 2022).…”
Section: Introductionmentioning
confidence: 99%